2016
DOI: 10.1051/matecconf/20178702007
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Tidal Energy Potential based on High and Low Tides for Sabah and Sarawak

Abstract: Abstract. Tidal energy is one of the best predictable and reliable source of renewable energy. Therefore, this paper aims to map extractable tidal energy, and to determine potential locations to generate electricity from tidal power along the coastline of Sabah and Sarawak states of Malaysia. The data was obtained from Sarawak Marine Department, and analyzed by using ArcGIS version 10.3. There are two potential locations, namely Tawau in Sabah, and Pending in Sarawak, where 67.0kW and 115.4kW of optimum power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Winds, currents and wave patterns are influenced by the northeast monsoon, which usually occurs from November to March, bringing more rainfall, and the southwest monsoon, which prevails from May to September, causing warmer and drier conditions (Defense Mapping Agency, 1994;Saleh et al, 2010;Samrat et al, 2014;Sentian et al, 2019). The coastal regions of the South China Sea and Sulu Sea experience diurnal tides with a tidal range of ~2 m; in contrast, coastlines along the Celebes Sea region have semi-diurnal tides, with a tidal range of >3 m in the southeast (DHI, 2005;Samo et al, 2017). Seawater in this region is consistently warm with an average sea surface temperature of about 24°C to 32°C (Lim et al, 2009).…”
Section: Environmental Settingmentioning
confidence: 99%
“…Winds, currents and wave patterns are influenced by the northeast monsoon, which usually occurs from November to March, bringing more rainfall, and the southwest monsoon, which prevails from May to September, causing warmer and drier conditions (Defense Mapping Agency, 1994;Saleh et al, 2010;Samrat et al, 2014;Sentian et al, 2019). The coastal regions of the South China Sea and Sulu Sea experience diurnal tides with a tidal range of ~2 m; in contrast, coastlines along the Celebes Sea region have semi-diurnal tides, with a tidal range of >3 m in the southeast (DHI, 2005;Samo et al, 2017). Seawater in this region is consistently warm with an average sea surface temperature of about 24°C to 32°C (Lim et al, 2009).…”
Section: Environmental Settingmentioning
confidence: 99%
“…Tidal energy sources in these locations can reach about 10% of the total electricity demand in Malaysia which is 83,000 GWh/year [1]. According to findings from Minerals and Geoscience Department Malaysia, Universiti Malaya, Universiti Teknologi Malaysia and Universiti Malaysia Sarawak [49], [113], [114], areas such as Pulau Langkawi, Pulau Pangkor, Pelabuhan Klang, Malacca, and Sandakan have a minimum flow rate of 0.4 m/s [1]. Whereas in Sabah and Sarawak, the potential areas for tidal turbine are in Sejingkat, Sibu; Pending, Tawau, Kota Belud, Pulau Jambongan [1], [113].…”
Section: B Potential Site Of Tidal Stream Energy In Malaysiamentioning
confidence: 99%
“…According to findings from Minerals and Geoscience Department Malaysia, Universiti Malaya, Universiti Teknologi Malaysia and Universiti Malaysia Sarawak [49], [113], [114], areas such as Pulau Langkawi, Pulau Pangkor, Pelabuhan Klang, Malacca, and Sandakan have a minimum flow rate of 0.4 m/s [1]. Whereas in Sabah and Sarawak, the potential areas for tidal turbine are in Sejingkat, Sibu; Pending, Tawau, Kota Belud, Pulau Jambongan [1], [113]. Samo et al [113] found that Pending location can generate a great amount of 115.4 kW tidal energy in the Sarawak coastline and follow by Tawau with the amount of 67.0kW tidal energy in Sabah coastline.…”
Section: B Potential Site Of Tidal Stream Energy In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations